Verbal social support for newly diagnosed breast cancer patients during surgical decision-making visits. (1st October 2016) - Nazione, Samantha; Silk, Kami J.; Robinson, Jeffrey
Abstract: This study reports an analysis of verbal social support strategies directed by surgeons and patients' companions to breast cancer patients using the social support behavior code. Additionally, the influence of companions on the provision of social support is examined. Forty-six videotapes of appointments where treatment regimens were being decided were analyzed. Results demonstrated that the majority of units spoken by surgeons were coded as verbal social support, primarily in the form of informational social support. Companions' social support was lower (relative to surgeons) in nearly every category of social support assessed. Patients who brought companions were found to receive more network social support from surgeons. Overall, these results point to low emotional support from surgeons and companions for patients during these appointments, which indicates a need for modifications in empathy training for medical providers.